SCHOOL REFORMS IN THE UK: REALISATION OF COMPETENCE APPROACH IN TEACHING STUDENTS AT THE KEY STAGE FOUR - Андрєєв, Сергій Андрійович (Scientific notes of the pedagogical department, 2015)
The article reveals the problem of school reforms in the UK that has been starting since 2002. The paper also analyses the experience of state school reforms and their positive and negative results in the frame of competence approach.